2011
DOI: 10.1016/j.jet.2010.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Measuring school segregation

Abstract: Using only ordinal axioms, we characterize several multigroup school segregation indices: the Atkinson Indices for the class of school districts with a given fixed number of ethnic groups and the Mutual Information Index for the class of all districts. Properties of other school segregation indices are also discussed. In an empirical application, we document a weakening of the effect of ethnicity on school assignment from 1987/8 to 2007/8. We also show that segregation between districts within cities currently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
149
0
16

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(167 citation statements)
references
References 37 publications
(73 reference statements)
2
149
0
16
Order By: Relevance
“…As these contributions do not contain the segregation that arises from the interaction between ethnicity and gender, the withinterms can be considered the marginal e ects of either ethnicity or gender on overall segregation. 9 8 See Author2 and Author3 (2011) for the proof of this result in the case with only two groups and Frankel and Volij (2011) for the multigroup case.…”
Section: An Approach Based On the Mutual Information Indexmentioning
confidence: 96%
See 4 more Smart Citations
“…As these contributions do not contain the segregation that arises from the interaction between ethnicity and gender, the withinterms can be considered the marginal e ects of either ethnicity or gender on overall segregation. 9 8 See Author2 and Author3 (2011) for the proof of this result in the case with only two groups and Frankel and Volij (2011) for the multigroup case.…”
Section: An Approach Based On the Mutual Information Indexmentioning
confidence: 96%
“…As indicated in the Introduction, Frankel and Volij (2011) have shown that the M index is the only segregation index that, in addition to possessing other desirable properties, satis es the SGD property. 6 Therefore, the remainder of this Section is devoted to a brief presentation of the M index and its properties relevant to this study.…”
Section: An Approach Based On the Mutual Information Indexmentioning
confidence: 97%
See 3 more Smart Citations